The 2005 Galápagos humpback whale expedition: a first attempt to assess and characterise the population in the Archipelago - Félix, Fernando; M. Palacios, Daniel; K. Salazar, Sandie; Caballero, Susana; Haase, Ben; Falconí, Jéssica (J. Cetacean Res. Manage., 2020)
It has been known for some time that humpback whales (Megaptera novaeangliae) occur in waters of the Galápagos Islands, an oceanic archipelago located 1,000km west of Ecuador, South America (1°S, 91°W), but their presence there has been poorly documented. Although presumed, no linkage has been established between Galápagos and southeast Pacific humpback whales (Breeding Stock G), the nearest breeding stock. An expedition to Galápagos was carried out between 31 August and 10 September 2005 to document the presence of humpback whales, their distribution, and their relationship to other stocks in the Pacific. Surveys covered 722km of the central and southern parts of the archipelago. Only one adult with a newborn calf was found at Santa Fé Island (0°47’S, 90°05.1’W), yielding an encounter rate of 0.27 whales per 100km of survey. A hydrophone with a response frequency range of 0.25–25kHz was dropped 25 times, but no whale sounds were heard. A skin sample was obtained by darting of the adult at Santa Fé, and was used for genetic analysis of the mtDNA control region. The haplotype of the Galápagos specimen has been found in a few individuals sampled previously off Colombia, Ecuador and the Antarctic Peninsula, thus establishing at least some degree of relatedness with Breeding Stock G. The observations, combined with a compilation of historical and recent sighting information in the archipelago, support the idea that Galápagos is a breeding area for the species. Further studies are needed to establish the level of discreteness, size and other basic aspects of the Galápagos humpback whale population.